SINBAD-ARES - A Photo-Injector for external Injection Experiments in novel Accelerators at DESY. (July 2020) - Marchetti, Barbara; Assmann, Ralph; Brinkmann, Reinhard; Burkart, Florian; Dorda, Ulrich; Floettmann, Klaus; Hartl, Ingmar; Hillert, Wolfgang; Huening, Markus; Jafarinia, Farzad; Jaster-Merz, Sonja; Kellermeier, Max; et al.
Abstract: The accelerator R&D facility SINBAD (Short Innovative Bunches and Accelerators at DESY) will drive multiple independent experiments in the fields of production of ultra-short electron bunches and tests of advanced high gradient acceleration concepts. The SINBAD-ARES (Accelerator Research Experiment at SINBAD) linac has been designed to allow the production of high brightness ultra-short electron bunches with excellent arrival-time stability. The accelerator will be used to study experimentally the optimization of the brightness for fs long electron bunches. Such electron bunches, with tunable characteristics, will be then injected into novel accelerators realized in the context of the ATHENA project, the ACHIP international collaboration and the ARIES program. In this paper we describe the principal characteristics of the linac design, we underline the technical challenges connected to the production and characterization of fs bunches and we report on the status of the installation and commissioning.